Developing the positive performance of satellite channels by improving product presentation processes in their television programmes (Journal of Namibian Studies : History Politics Culture, 2023)
In the age of communications that we live in, many technological developments have taken place in the field of broadcasting, as in every field. With these developments, broadcast quality has increased and the number of TV channels has increased, with the digital method of programming in particular, the fact that the audience can watch the broadcast they want at any time has resulted in the ad generation going by without watching it, and as a result, reaching and keeping consumers more difficult. to the content of the message. In light of all these developments, brands have sought to convey their messages by reaching consumers through alternative channels other than traditional advertising channels in their media strategies (Chalaby, J. K. (2016)). As a result of these searches, applications that we call product placement, which can be defined as “the integration of branded products with communication media such as series, TV shows, music videos, video games, computer games, and especially movies”, have become such the practices are "alternatives to traditional forms of marketing communications that are becoming more expensive and less efficient in reaching target audiences."